Model Pembentukan Karakter Keagamaan Melalui Program Unggulan Al-Ihya' Li 'Ulumi Ad-Din di MTs Salafiyah Syafi'iyah Tebuireng Jombang - Nadlifah Rizki Utami; Abdullah Aminuddin Aziz (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2019)
MTs Salafiah Tebuireng Jombang is an Islamic-based school that is expected not only to be able to play a role in equipping and developing general knowledge and religious knowledge, but also being able to carry out its role to change that knowledge into meaningful and valuable ways through various schools. Internalize the values ​​of Islamic religious education so that they can control students in acting and behaving religiously in their daily lives. In the age of globalization that is full of these challenges, education seems to be getting heavier with the demands of increasingly complex modern society. The impact of educators must be to keep pace with the times that are increasingly creative and dynamic, but still maintain Islamic values. Planting Islamic values ​​through education is very necessary for students. The many deviant behaviors of students and adolescents in general that are not in accordance with religious norms lately encourage various parties to question the effectiveness of the implementation of religious education in schools. Islamic Education must be an agent of change in changing the behavior of students in a better direction. Based on the description above, several problems can be formulated, namely: 1) How is the religious character education of students at Salafiyah Syafi'iyah Tebuireng Jombang MTs, 2) How is the formation of religious character of students through the flagship program Al-Ihya’ Li ‘Ulumi ad-Din, and 3) What are the supporting and inhibiting factors for the formation of the religious character of students through the Al-Ihya' 'Li-Ulumi Ad-Din program. The type of research used by the author is a case study, the approach uses a descriptive qualitative approach, while the method used is the method of observation, interviews and documentation. From the results of this study it was concluded that the process of internalizing the values ​​of Islamic religious education in shaping the Muslim personality of students at the MTs Salafiyah Syafi'iyah Tebuireng Jombang was: in the first hour students read the Qur'an, Asma'ul Husna and prayers, rest first prayer in dhuha, resting of the two dzuhur prayers in congregation and culture, carrying out PHBI activities, holding religious competitions in the month of Ramadan, teachers deepening learning material, being familiar with students, giving taladan, monitoring students, material delivered in accordance with the Qur'an and the hadith, students are required to memorize the verses in the Qur'an and hadith according to the material being taught, students are given the task to read the Qur'an every day for at least 10 verses, students take part in religious extracurricular activities